Tropical fruit wastes as an organic nutrient sources for the cultivation of chlorella vulgaris and haematococcus pluvialis - Tan Y.H.; Khoo Y.J.; Chai M.K.; Wong L.S. (Technoscience Publications, 2023)
Algae; Biomass; Microorganisms; Nutrients; Tropics; Biomass concentrations; Chlorella vulgaris; Haematococcus pluvialis; Nutrient supplements; Organic nutrients; Specific growth rate; Tropical fruits; Waste medium; Fruits; bacterium; biomass; concentration (composition); cultivar; cultivation; detection method; growth rate; Ananas comosus; Carica papaya; Chlorella vulgaris; Haematococcus pluvialis; Pluvialis